Comparative Analysis of Energy Use and Greenhouse Gas Emission of Diesel and Electric Trucks for Food Distribution in Gowanus District of New York City - Elangovan, Raghul; Kanwhen, Ondrea; Dong, Ziqian; Mohamed, Ahmed; Rojas-Cessa, Roberto (Frontiers in Big Data, 2021)
New York City’s food distribution system is among the largest in the United States. Food is transported by trucks from twelve major distribution centers to the city's point-of-sale locations. Trucks consume large amounts of energy and contribute to large amounts of greenhouse gas emissions. Therefore, there is interest to increase the efficiency of New York City's food distribution system. The Gowanus district in New York City is undergoing rezoning from an industrial zone to a mixed residential and industrial zone. It serves as a living lab to test new initiatives, policies, and new infrastructure for electric vehicles. We analyze the impact of electrification of food-distribution trucks in terms of the greenhouse gas emission and the electricity demand in this district in this paper. However, such analysis faces the challenges of accessing available and granular data, modeling of demands and deliveries that incorporate logistics and inventory management of different types of food retail stores, delivery route selection, and delivery schedule to optimize food distribution. We propose a framework to estimate truck routes for food delivery at a district level. We model the schedule of food delivery from a distribution center to retail stores as a vehicle routing problem using an optimization solver. Our case study shows that diesel trucks consume 300% more energy than electric trucks and generate 40% more greenhouse gases than diesel trucks for food distribution in the Gowanus district.